Massively multiplayer online role-playing games as arenas for second language learning - Peterson, Mark (Computer Assisted Language Learning, 2010)
This article investigates contemporary research on the use of massively multiplayer online role-playing games (MMORPGs) in language education. The development and key features of these games are explored. This is followed by an examination of the theories proposed as a basis for game-based learning, and the claims made regarding the value of utilizing network-based gaming in computer assisted language learning (CALL). A critical analysis of three influential learner-based studies drawn from the literature is then undertaken. This reveals that present research is largely exploratory in nature and is subject to limitations. The analysis draws attention to the role played by learner training and indicates that for intermediate and advanced level English language learners, MMORPGs offer a motivating context that elicits engagement in beneficial forms of target language interaction. Research further suggests that learner participation in network-based gaming provides valuable opportunities for vocabulary acquisition and the development of communicative competence. This article concludes by highlighting the urgent need for additional studies and identifies areas with potential in future research.